Musical Thinking, the Uniqueness of Music Culture, the Understanding of its Laws and the Specific Features of Understanding the Content of Musical Works of Art - Yusupjonova daughter of Dilfuzakhan Olimjon; Anvarova daughter of Barnokhan Dilshodjon (European Science Publishing, 2023)
This article discusses the concept of national music in society and their place in life, as well as the immense need for the development of a highly spiritual society.